2011
DOI: 10.1021/jp2006342
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence Enhancement in Polymer Light-Emitting Diodes through Inelastic Scattering of Oppositely Charged Bipolarons

Abstract: Combining the one-dimensional tight-binding Su-Schrieffer-Heeger (SSH) model and the extended Hubbard model (EHM), the scattering and combination of oppositely charged bipolarons in conjugated polymers are investigated using a nonadiabatic evolution method. On the basis of this physical picture, bipolarons can scatter into a singlet biexcitonic state, in which two electrons and two holes are trapped together by a lattice distortion. This biexcitonic state can emit one photon to an exciton state, which can subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
2
27
2
Order By: Relevance
“…Alongside the new excited species yielded in the present study, other kind of beasts, such as excitons and biexcitons, were also obtained. As these later ones were already observed in other theoretical studies reported in literature 7,8,31–35 , their behavior, although of importance, will not be focus of our attention here in favor of discussing the previously unreported channel. In the numerical realizations performed in the present work, the new found product is noted to take place for U , α , and E 0 ranging between 1.0–4.0 eV, 4.6–5.6 eV/Å, and 1.0–1.5 mV/Å, respectively.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Alongside the new excited species yielded in the present study, other kind of beasts, such as excitons and biexcitons, were also obtained. As these later ones were already observed in other theoretical studies reported in literature 7,8,31–35 , their behavior, although of importance, will not be focus of our attention here in favor of discussing the previously unreported channel. In the numerical realizations performed in the present work, the new found product is noted to take place for U , α , and E 0 ranging between 1.0–4.0 eV, 4.6–5.6 eV/Å, and 1.0–1.5 mV/Å, respectively.…”
Section: Resultssupporting
confidence: 53%
“…This kind of quasi-particle, in turn, is spinless and present charge ±3 e . It is already well accepted that an electron-bipolaron (negatively charged particle) and a hole-bipolaron (positively charged particle) may recombine to form a mixed state composed of bipolarons and excitons 710 . The light emission phenomenon results from the radiative decay of this kind of excited particle.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies has been carried out on the dynamics of scattering involving opposite charged quasi-particles [7][8][9][10][11], but we could not find any on quasi-particles with same sign charges. The present work addresses such situations in pristine chains of cispolyacetilene and polyparaphenylene, both simple and prototypical polymers whose analysis is relatively easy and can shed light on more complex systems.…”
contrasting
confidence: 61%
“…has previously shown, synthesis of PEDOT nanoparticles using soft templating leads to oxidation of the particles corresponding to strong NIR absorption due to polaron and bipolaron formation . Polaron decay is ideal for enhancing the photothermal potential of PEDOT for medical use . Both PEDOT NS and NF have broad optical absorption throughout the infrared region, as shown in Figure .…”
Section: Resultsmentioning
confidence: 92%
“…8 Polaron decay is ideal for enhancing the photothermal potential of PEDOT for medical use. [44][45][46] Both PEDOT NS and NF have broad optical absorption throughout the infrared region, as shown in Figure 2. The Raman spectrum of our synthesized NF, as shown in Figure 3, matches closely with the signature of commercially purchased PEDOT nanotubes, even though the commercial material has a more rounded "pillow-type" instead of tubular morphology.…”
Section: Optical and Thermal Propertiesmentioning
confidence: 96%